A review on engineering polymer drug conjugates to improve combination chemotherapy. (September 2017) - Vogus, Douglas R.; Krishnan, Vinu; Mitragotri, Samir
Abstract: Combination chemotherapy treatments with polymer drug conjugates (PDCs) have been designed to overcome the limitations of traditional chemotherapy. While there are many significant design challenges associated with engineering a combination therapy with PDCs, several studies have shown therapeutic benefits of incorporating multiple drugs onto a polymeric carrier. Here, we summarize the chemistries and biological performance of different combination PDCs that have been tested in the preclinical setting and offer recommendations for future studies which will provide the necessary information to streamline future translation. Graphical abstract: